A belief-based theory of homophily - Kets, W; Sandroni, A (Elsevier, 2019)
Homophily, the tendency of people to associate with people similar to themselves, is a widespread phenomenon that has important economic consequences. We endogenize players' preferences for interacting with their own group by modeling the process by which players take others' perspective. Homophily emerges because players find it easier to put themselves into the shoes of members of their own group. The model sheds light on various empirical regularities and has novel welfare implications. In particular, policies that reduce homophily may not improve social welfare.